Impact of corporate governance and CEO remuneration on bank capitalization strategies and payout decision in income shocks period - Xiang, Hangqin; Shaikh, Erum; Tunio, Muhammad Nawaz; Watto, Waqas Ahmad; Lyu, Yiqing (Frontiers in Psychology, 2022)
The purpose of this research corporate governance and CEO remuneration with banks capitalization strategies and payout policy Pakistani banking context. Data is obtained from financial statements of schedule banks listed on the Pakistan stock exchange from 2005 to 2020. The findings of the research study reveal that corporate governance mechanisms that promote the bank's shareholders' interests are linked to low capitalization strategies. The size of the board of directors has a detrimental impact on the capitalization of banks. Banks’s capitalization techniques are also adversely correlated with effective board size. The shareholder benefits from low capitalization. Corporate governance is positively related with banking sector instability, as seen by this negative correlation. Bank capitalization strategies have a detrimental impact on CEO remuneration. In the event of an income shock, the payout is essential. Banking sector payout policies are negatively related with corporate governance. In the event of a negative income shock, financial institutions reduce dividends. As a result, it's been argued that effective corporate governance benefits shareholders by reducing capitalization tactics and limiting financial institutions' aggressive payouts.